2017
DOI: 10.1002/biot.201700286
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling Based PAT Implementation for Ion‐Exchange Process Chromatography of Charge Variants of Monoclonal Antibody Products

Abstract: Process chromatography is typically used to remove product related impurities and variants that have very similar physicochemical properties to the product. Baseline separation may not be achieved in most cases due to high protein loading and thus, pooling of the elution peak can be challenging for maximizing yield and achieving consistency in product quality. Batch-to-batch variability in quality of the feed material also occurs in commercial manufacturing. Mechanistic modeling of process chromatography, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…This is because most PAT applications in recent literature require flexibility in unit operation flowrates, and can only be implemented if surge tanks are present to decouple the process flow streams. Examples of such PAT approaches include variable loading in Protein A chromatography to handle upstream titer variations (Rathore et al, 2019; Rüdt et al, 2016; Thakur, Hebbi, & Rathore, 2020), variable pooling in polishing chromatography in case of changes to the product charge variant profile (Kumar & Rathore, 2017; Tiwari et al, 2018), or variable flowrate and pressure in ultrafiltration to handle membrane fouling and concentration deviations (Thakur, Thori, et al, 2020; van Reis et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…This is because most PAT applications in recent literature require flexibility in unit operation flowrates, and can only be implemented if surge tanks are present to decouple the process flow streams. Examples of such PAT approaches include variable loading in Protein A chromatography to handle upstream titer variations (Rathore et al, 2019; Rüdt et al, 2016; Thakur, Hebbi, & Rathore, 2020), variable pooling in polishing chromatography in case of changes to the product charge variant profile (Kumar & Rathore, 2017; Tiwari et al, 2018), or variable flowrate and pressure in ultrafiltration to handle membrane fouling and concentration deviations (Thakur, Thori, et al, 2020; van Reis et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…For well-predicted systems, Kumar and Rathore [90] demonstrated that mechanistic model simulations conducted prior to running the separation can be used to dictate fractionation. This feedforward control strategy was dependent on the availability of feed composition data, which in this case was obtained using UPLC.…”
Section: Mechanistic Modelling For Chromatography Controlmentioning
confidence: 99%
“…In an industrial setting however, feed data may be readily accessible from the upstream operation. A more computationally efficient fractionation method using mechanistic model simulations of the product profile only and an in-line UV signal was also demonstrated [90]. The difference between the overall UV signal and the mechanistic model prediction of the product profile was used as a measure of the impurity content.…”
Section: Mechanistic Modelling For Chromatography Controlmentioning
confidence: 99%
“…In addition to the capability of mechanistic models in downstream process development, they have also been used for monitoring of biopharmaceuticals and their impurities. For example, monoclonal antibodies and their variants have been modeled in size exclusion chromatography, cation exchange chromatography, and hydrophobic interaction chromatography . The agreement of these mechanistic models with experimental data demonstrates their potential as monitoring tools.…”
Section: Introductionmentioning
confidence: 99%
“…For example, monoclonal antibodies and their variants have been modeled in size exclusion chromatography, 20 cation exchange chromatography, [21][22][23][24][25][26] and hydrophobic interaction chromatography. 27,28 The agreement of these mechanistic models with experimental data demonstrates their potential as monitoring tools.…”
mentioning
confidence: 99%